Description of three new species of Bradyidius (Copepoda: Calanoida), the new aetideids from the deep Pacific Ocean, with notes on the genera Bradyidius and Aetideopsis - Markhaseva, Elena L.; Renz, Jasmin (Zootaxa, 2021)
Three new aetideid species, Bradyidius abyssalis sp. nov., Bradyidius parabyssalis sp. nov., and B. kurilokamchaticus sp. nov. are described from female specimens collected near the seafloor in the abyss of the Pacific and Atlantic Oceans. Specimens of Bradyidius parabyssalis sp. nov. were obtained in both the Atlantic and Pacific Oceans (Argentine Basin, area of the Meteor Seamount and the Kurile-Kamchatka Trench). Bradyidius abyssalis sp. nov. was found only in the Atlantic Ocean, (Brazil and Guinea Basins and area of the Meteor Seamount) and Bradyidius kurilokamchaticus sp. nov. was recorded from the Kurile-Kamchatka Trench of the Pacific Ocean. Three new herein described Bradyidius species constitute the first documented records of the genus from the abyss of the World Ocean. In addition, three Bradyidius species from the Weddell Sea, the Atlantic Ocean and the Kurile-Kamchatka Trench, are briefly described without biological names due to their bad condition. Bradyidius parabyssalis sp. nov. and B. abyssalis sp. nov. are distinguished from all known congeners by the presence of 3 setae at the basis of the mandible and morphological details of the prosome posterior corners and P1. They show close resemblance to each other but differ in body size, rostrum structure, P4 coxa armament and length of the setae of the antennule ancestral segment I and the mandible basis. Bradyidius kurilokamchaticus sp. nov. shares with B. curtus Markhaseva, 1993, B. pacificus (Brodsky, 1950) and B. arnoldi Fleminger, 1957 a rostrum with non-divergent or parallel points, but differs from these species in the size, the well developed lateral spine on exopod segment 1, in the number of setae at the antenna exopod segment 1 and some morphological details of the prosome posterior corners. Characters that define the genus Bradyidius Giesbrecht, 1897 from Aetideopsis Sars, 1903, i.e. the shape of lateral spines of P1exopod segments 1 and 2; the endopod of P2 segmentation and the setation of the antennule ancestral segments XII, XV and XVII are discussed.